Answer:
![\frac{(x)^{2}}{49}+\frac{(y)^{2}}{1}=1](https://tex.z-dn.net/?f=%5Cfrac%7B%28x%29%5E%7B2%7D%7D%7B49%7D%2B%5Cfrac%7B%28y%29%5E%7B2%7D%7D%7B1%7D%3D1)
Step-by-step explanation:
In this problem we have a horizontal ellipse, because the major axis is the x-axis
The equation of a horizontal ellipse is equal to
![\frac{(x-h)^{2}}{a^{2}}+\frac{(y-k)^{2}}{b^{2}} =1](https://tex.z-dn.net/?f=%5Cfrac%7B%28x-h%29%5E%7B2%7D%7D%7Ba%5E%7B2%7D%7D%2B%5Cfrac%7B%28y-k%29%5E%7B2%7D%7D%7Bb%5E%7B2%7D%7D%20%3D1)
where
(h,k) is the center of the ellipse
a and b are the respective vertices distances from center
we have
vertices at (7, 0) and (-7, 0)
co-vertices at (0, 1) and (0, -1)
so
The center is the origin (0.0) (The center is the midpoint of the vertices)
a=7
b=1
substitute
![\frac{(x-0)^{2}}{7^{2}}+\frac{(y-0)^{2}}{1^{2}}=1](https://tex.z-dn.net/?f=%5Cfrac%7B%28x-0%29%5E%7B2%7D%7D%7B7%5E%7B2%7D%7D%2B%5Cfrac%7B%28y-0%29%5E%7B2%7D%7D%7B1%5E%7B2%7D%7D%3D1)
![\frac{(x)^{2}}{49}+\frac{(y)^{2}}{1}=1](https://tex.z-dn.net/?f=%5Cfrac%7B%28x%29%5E%7B2%7D%7D%7B49%7D%2B%5Cfrac%7B%28y%29%5E%7B2%7D%7D%7B1%7D%3D1)